Vaspin and lipocalin-2 levels in severe obsructive sleep apnea. - KISKAÇ, MUHARREM; KıSKAÇ, MUHARREM; ZORLU, MEHMET; ZORLU, MEHMET; AKKOYUNLU, MUHAMMED EMİN; AKKOYUNLU, MUHAMMED EMİN; KILIÇ, ERDEM; KILIC, ERDEM; KARATOPRAK, CUMALİ; CAKIRCA, MUSTAFA; ÇAKIRCA, MUSTAFA; Karatoprak, CUMALİ; et al. (My University, 2014)
Background: Vaspin and lipocalin-2 are less-known recent members of adipocytokine family. There are ongoing studies investigating the role of vaspin ve lipocalin-2 in metabolic syndrome (MS). Obstructive sleep apnea syndrome (OSAS) is independently associated with an increased prevalence of MS. We aimed to measure the levels of vaspin and lipocalin-2 which are secreted from adipocytes in patients with severe OSAS and examine the relationship between these two adipocytokines and OSAS. Methods: The study consisted of two groups: severe OSAS patients with an apnea-hypopnea index (AHI) of >30/h (OSAS group, 34 subjects) and age-matched healthy volunteers with a AHI <5/h (control group, 25 subjects) Serum levels of vaspin and lipocalin-2 in these two groups were compared. Results: Serum levels of vaspin were significantly lower in OSAS group; patients with severe OSAS compared with control group; healthy volunteers (OSAS group: 0.69±0.5 vs. control group: 1.24±1.13; P=0.034). The difference between the two groups in terms of serum levels of lipocalin-2 has not reached statistical significance (OSAS group: 61.6±18.2 vs. control group: 68.5±20.1; P=0.17). Conclusions: We found that serum vaspin levels were significantly lower in patients with severe OSAS compared with healthy controls. Lipocalin-2 levels were similar. The decrease in serum vaspin levels in severe OSAS patients may be important in diagnosis and follow-up of these patients.